2018
DOI: 10.1016/j.bbadis.2018.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic identification of altered protein O-GlcNAcylation in a triple transgenic mouse model of Alzheimer's disease

Abstract: PET scan analysis demonstrated the early reduction of cerebral glucose metabolism in Alzheimer disease (AD) patients that can make neurons vulnerable to damage via the alteration of the hexosamine biosynthetic pathway (HBP). Defective HBP leads to flawed protein O-GlcNAcylation coupled, by a mutual inverse relationship, with increased protein phosphorylation on Ser/Thr residues. Altered O-GlcNAcylation of Tau and APP have been reported in AD and is closely related with pathology onset and progression. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 83 publications
1
26
0
Order By: Relevance
“…Studies on human AD brain showed a marked decrease in tau-specific and global levels of O-GlcNAcylation, which are associated with the decline of (1) cerebral glucose metabolism, (2) brain insulin signaling and (3) neuronal GLUTs expression [5,6,9], suggesting that the O-GlcNAc modification of protein could represent the link between glucose hypometabolism and NFT formation. Furthermore, aberrant O-GlcNAc levels have been found on several proteins involved in glucose metabolism, strengthening this link [10,11]. Besides, aberrant levels of O-GlcNAc has been reported also on APP implying that this modification could be involved in the induction of its nonamyloidogenic processing by γ-secretase and to the formation of senile plaques [12].…”
Section: Protein O-glcnacylation and Tauopathiesmentioning
confidence: 92%
See 1 more Smart Citation
“…Studies on human AD brain showed a marked decrease in tau-specific and global levels of O-GlcNAcylation, which are associated with the decline of (1) cerebral glucose metabolism, (2) brain insulin signaling and (3) neuronal GLUTs expression [5,6,9], suggesting that the O-GlcNAc modification of protein could represent the link between glucose hypometabolism and NFT formation. Furthermore, aberrant O-GlcNAc levels have been found on several proteins involved in glucose metabolism, strengthening this link [10,11]. Besides, aberrant levels of O-GlcNAc has been reported also on APP implying that this modification could be involved in the induction of its nonamyloidogenic processing by γ-secretase and to the formation of senile plaques [12].…”
Section: Protein O-glcnacylation and Tauopathiesmentioning
confidence: 92%
“…A foster crucial restrain, in considering the use of OGA inhibitors as a valuable therapeutic strategy for tau-related pathologies, is represented by the variability of O-GlcNAc levels alteration in pathological brains, as recently observed. Data collected so far, on AD brains from human and mouse models of the disease, suggest that the cytoplasmic and mitochondrial proteome of the hippocampal region represents one of the primary target of intervention [6,9,10], indicating that a brain region-specific administration strategy focusing on these areas should be preferred to a systemic delivery (by oral or intraperitoneal injection distribution). Hence, a targeted administration could allow to maximize the effects, rescue cognition, and avoid the modification of unaffected brain regions or peripheral organs.…”
Section: Therapeutic Modulation Of Protein O-glcnacylationmentioning
confidence: 99%
“…Tau-O-GlcNAc is neuroprotective whilst its hyperphosphorylation leads to the formation of the toxic NFTs observed in AD human and mouse brain [ 106 ]. A triple transgenic murine model of AD (3 × Tg-AD), which develop age-dependent and region-specific Aβ and tau aggregations that closely mimic the disease progression seen in humans, represents a valuable model for the study of O-GlcNAcylation [ 23 , 108 , 109 , 110 , 111 , 112 , 113 ]. In this regard, 12-month-old 3 × Tg-AD mice exhibited reduced levels of tau O-GlcNAcylation, which is consistent with tau hyperphosphorylation at Ser396 and Thr205 in the hippocampus [ 22 ].…”
Section: Glycosylation In Alzheimer’s Diseasementioning
confidence: 99%
“…These data suggest that tau-O-GlcNAc and tau phosphorylation are inversely related and have opposite effects, which suggests that O-GlcNAc is a possible novel therapeutic target in AD. Tramutola and colleagues reported an increase of OGA enzyme activity in 3 × Tg-AD, coupled with the decrease of total O-GlcNAcylation levels, which could translate as an increased removal of GlcNAc residues from proteins [ 23 ]. The pharmacological inhibition of OGA with Thiamet-G in the JNPL3 tauopathy mouse model resulted in increased tau O-GlcNAc and decreased neuronal cell loss and tau aggregate formation [ 114 , 115 ].…”
Section: Glycosylation In Alzheimer’s Diseasementioning
confidence: 99%
See 1 more Smart Citation